Penerapan Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Untuk Meningkatkan Hasil Belajar Mata Pelajaran IPA Pada Siswa Kelas V MI Al-Kifayah Pekanbaru - Supri, Supri; Purnamasari S, Ayu; Imroatul Jamilah, Ika (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
The research purpose is to describe the application of Numbered Head Together (NHT) to improve students’ science achievement at the third grade students of MI Al-Kifayah Pekanbaru. The subjects of this study were 20 students at fifth grade of MI Al-Kifayah Pekanbaru consist of 5 boys and 15 girls in heterogeneous student abilities. Meanwhile, the object of this research is to improve students’ science achievement through the application of the Numbered Head Together, one of type of cooperative learning model. The research procedure used Classroom Action Research. In order to ensure this classroom action research run well, the researcher used the steps; 1) Planning/preparing for action, 2) Action implementation, 3) Observation, and 4 ) Reflection. The results of the study proved that the application of the numbered head together type of cooperative learning model in fifth grade of MI Al-Kifayah Pekanbaru. The result of the research showed that there is an increase in students’ science achievement before the action to cycle I and cycle II. Before the action, before the action to cycle I and cycle II, only 40%. students who reached criteria level minimum (KKM). In the first cycle the student who reached criteria level minimum (KKM ) became 75% and in the second cycle students who reached criteria level minimum (KKM) increased to 90%. It proved that improvement of students’ science achievement of fifth grade students of Madrasah Ibtidaiyah Al-Kifayah Pekanbaru by applying the numbered head together type of cooperative learning model is considered well done as the individual and class reached 90% of criteria level minimum (KKM).